Google Sites Interactive Multimedia Improves Elementary Islamic Education Outcomes: Multimedia Interaktif Google Sites Meningkatkan Hasil Belajar PAI Sekolah Dasar - Ade Yusup; din wahyudin; iman nasrulah; Deni Darmawan; Dian Rahadian; Ayu Puji Rahayu (Academia Open, 2026)
General Background: Islamic Religious Education (PAI) plays a strategic role in shaping students’ character, morality, and spirituality at the elementary level. Specific Background: However, PAI learning is often constrained by conventional methods, limited instructional media, and low student engagement, resulting in suboptimal learning outcomes. Knowledge Gap: Previous studies have predominantly focused on general subjects and secondary education, with limited research examining Google Sites–based interactive multimedia specifically for PAI in elementary schools with comprehensive evaluation. Aims: This study aims to develop and evaluate Google Sites–based interactive multimedia in terms of feasibility, practicality, and learning outcomes in PAI. Results: Using the ADDIE model and data from validation, student responses, and pretest–posttest analysis, the multimedia achieved high feasibility (average 95.1%), strong practicality (94.5%), and significant improvement in learning outcomes (mean score increased from 64.8 to 85.6; Wilcoxon significance 0.000). Novelty: The study provides a context-specific development of web-based interactive multimedia tailored to elementary PAI learning with comprehensive validation and testing. Implications: The findings indicate that Google Sites–based multimedia can serve as an accessible and structured digital learning medium supporting student engagement and improved academic performance in elementary Islamic education. Highlights• High feasibility achieved through expert validation across media, material, and instruction• Strong student response indicating ease of use, clarity, and attractive design• Significant score gains confirmed through nonparametric statistical testing KeywordsInteractive Multimedia; Google Sites; Learning Outcomes; Islamic Education; Elementary School